Incidence of infections associated with the use of invasive devices in an ICU after application of the Improvement Science Method - Vilto Michels Júnior; Jiliélisson Oliveira de Sousa; Gabriel Oscar Cremona Parma; Fabiana Schuelter-Trevisol; Daisson José Trevisol (Hospital de Clínicas de Itajubá, 2023)
Objective: To reduce the incidence density of ventilator-associated pneumonia (VAP), central line-associated bloodstream infection (CLABSI), and catheter-associated urinary tract infection (CAUTI) in the intensive care unit (ICU) using the Improvement Science method. Methods: This was a single-center retrospective cohort study. A collaborative quality improvement team developed and implemented local changes to HAI-related processes and protocols. Pre-intervention, intervention, and post-intervention periods were compared. The study was conducted at the Adult ICU of a hospital in southern Brazil. Variables were analyzed using interrupted time series analysis with segmented linear regression, simple correlation, and hypothesis testing. Results: There was a reduction in the incidence density of all infections. VAP was reduced from 27.2% to 7.2% (p < 0.001), CLABSI from 3.0% to 0.9% (p = 0.017), and CAUTI from 8.3% to 1.8% (p < 0.001). The ICU stay was also reduced from 6.7 to 6 days (p = 0.018). Conclusion: There was an improvement in all the evaluated parameters. Ongoing monitoring of related indicators and adherence to implemented measures are essential to sustain improvements. Applying the Improvement Science methodology can reduce the incidence of HAIs in the ICU.